Penguatan Partisipasi Masyarakat Dalam Penyelenggaraan Sekolah Di SMP Negeri 36 Rejang Lebong - Contesa, Emelia; Anwar, Syaiful (UNIVERSITAS BENGKULU, 2023)
This research aims to describe the initiation of community participation in the implementation of education at SMPN 36 Rejang Lebong. This research is a qualitative descriptive study. Research data was obtained from interviews, observation and documentation. Analysis of research data through data reduction, data presentation, verification and drawing conclusions. Based on the research results, it was concluded that: (1) What community participation is needed is harmonious communication with parents and trying to involve them in implementing school programs, (2) Conditions for community participation are running well. Communication between the community, whether the school community or the general public, is regulated by the public relations unit (PR). The public relations program is managed regularly and neatly, (3) Obstacles in managing community participation, namely if the community is involved in the implementation of school development, its performance or level of discipline is very low so it requires continuous supervision, because they are used to working in the village using a mutual cooperation or work system. with a contract system and being a contractor, work tends to be slow. (4) School autonomy provides bright prospects for increasing community participation in managing education in schools. Schools have broad authority in involving the role of the community in implementing school programs. Schools can provide opportunities for the community to participate according to their abilities. Suggestions that can be given are that schools can explore more widely the potential of the community whose participation in the provision of education can be developed so that they can improve both academic and non-academic achievements.